2015
DOI: 10.1055/s-0034-1398550
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Descending Serotonergic and Noradrenergic Systems and their Spinal Receptor Subtypes in the Antinociceptive Effect of Dipyrone

Abstract: The antinociceptive effect of dipyrone is partly due to its action upon pain-related central nervous system structures. Despite intensive research, the precise mechanisms mediating its analgesic effects remain unclear. Here, we aimed to determine whether neurotoxic destruction of descending inhibitory pathways affect dipyrone-induced antinociception and whether various spinal serotonergic and adrenergic receptors are involved in this antinociception. The nociceptive response was assessed by the tail-flick test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 32 publications
0
13
0
2
Order By: Relevance
“…Similarly, yohimbine also inhibited the antinociceptive activity of MECN when assessed using the same assay, hence suggesting that the antinociceptive activity of MECN is partly mediated via the α 2 adrenergic receptor activation. Meanwhile, previous studies have also reported on the participation of activated β -adrenergic receptors in central and peripheral nociceptive transmission [ 58 , 59 ]. In the present study, MECN-exerted antinociceptive activity was inhibited by pindolol, thus suggesting the modulation of MECN antinociceptive activity occurs partly via the activation of β- adrenergic receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, yohimbine also inhibited the antinociceptive activity of MECN when assessed using the same assay, hence suggesting that the antinociceptive activity of MECN is partly mediated via the α 2 adrenergic receptor activation. Meanwhile, previous studies have also reported on the participation of activated β -adrenergic receptors in central and peripheral nociceptive transmission [ 58 , 59 ]. In the present study, MECN-exerted antinociceptive activity was inhibited by pindolol, thus suggesting the modulation of MECN antinociceptive activity occurs partly via the activation of β- adrenergic receptors.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of such a large body of studies devoted to unveil the actual role of bulbo-spinal serotonergic pathways in the control of pain signaling, the situation is still confused to date. Thus, some authors ( Suzuki et al., 2004 , Rahman et al., 2006 , Wei et al., 2010 , Guo et al., 2014 ) concluded that these pathways are implicated in pain promoting mechanisms whereas others ( Yamazaki et al., 1999 , Hung et al., 2003 , Gencer et al., 2015 , Lee et al., 2015 ) reached the opposite conclusion, i.e. these pathways exerting an inhibitory influence on pain signaling.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the spasmogenic effects of areca nut can be blocked by atropine [29], which suggests that other systems, including muscarinic receptors, are also involved in the effects of areca nut. In addition, other types of 5-HT receptor and α1 adrenoceptors are involved in nociceptive modulation, and may play roles in the activity of areca nut [30,31]. Therefore, although the antiallodynic effects of areca nut have been validated by the current study, further research should be undertaken to investigate its detailed mechanisms of action and its influence on monoamines.…”
Section: Discussionmentioning
confidence: 81%